The masqueraders - Heyer, Georgette, frey50 (Naperville, Ill. : Sourcebooks Casablanca, 2009)
"Such a daring escape...could cost them both their hearts...Their infamous adventurer father has taught Prudence Tremaine and her brother Robin to be masters of disguise. Ending up on the wrong side of the Jacobite rebellion, brother and sister flee to London, Prudence pretending to be a dashing young buck, and Robin, a lovely young lady...Then Prudence meets the elegant Sir Anthony Fanshawe, and Robin becomes the mysterious hero of the charming Letitia Grayson, and in order to have what they truly want, the two masqueraders must find a way to unmask themselves without losing their lives..."--p.[4] of cover.
Keywords: Brothers and sisters; Man-woman relationships; Disguise; Great Britain -- History -- 18th century; Love stories; Regency fiction; Fiction; History